Self-care Management to Prevent Exacerbation for Patients with Chronic Obstructive Pulmonary Disease (COPD): A Systematic Review - Abdan Syakura; Nursalam Nursalam; Andri SW (Alta Dharma Publisher, 2020)
COPD is currently the number four cause of death in the world but is projected to be the third leading cause of death in 2020. The causes of recurrence are essential to be studiedbut prevention of recurrence is preferred in implementing prevention of recurrence in COPD patients. A systematic review of studies on the prevention of recurrence and the use of technology across the lifespan. The databases, Pubmed, Scopus, Elsevier, scholar, were systematically selected in this study. The authors independently rated the reporting of the qualitative studies included. Thematic synthesis was used to analyze the data. The search identified 330 papers. Eighteen research papers met the study inclusion criteria. The review revealed that self-management is an essential factor in reducing the recurrence of COPD sufferers. Alternative models of pulmonary rehabilitation are needed to improve equitable access and outcomes associated with patients. Telerehabilitation using information technology can achieve an equivalent increase in results compared to traditional pulmonary rehabilitation. It is efficient and cost-effective to rehabilitate; the proposed telerehabilitation model is designed to be applied appropriately into clinical practice. It takes a willingness and ability to carry out the prevention of recurrence of COPD sufferers. Knowledge and mastery of information technology are expected to improve the prevention of recurrence of COPD sufferers